2021
DOI: 10.1161/circ.144.suppl_2.14258
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 14258: Modulation of Kynurenine Pathway to Prevent Brain Injury After Cardiac Arrest and Cardiopulmonary Resuscitation in Mice

Abstract: Introduction: Kynurenine pathway (KP) is emerging as one of the potential components affecting cardiac arrest (CA) outcomes. The aim of this study is to evaluate the effects of KP inhibition through genetic deletion of the rate-limiting enzyme of the KP, indoleamine-2,3-dyoxygenase (IDO) on survival and neurological outcome after CA. Methods and Results: Sixteen adult male wild-type (WT) and IDO-deleted (IDO -/- ) mice were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With the development of metabolomics, research on the metabolomics of SCA is steadily increasing. At the animal level, researchers observed that targeting metabolic pathways such as kynurenine pathway 9 , ketone pathway 10 , mitochondrial energy 11 can attenuate brain injury after SCA, improve prognosis, and prolong survival in mice. Previous studies have also reported several circulating metabolite biomarkers in SCA patients: N-acetylaspartate/creatinine ratios, lactate levels, glucose level served as predictive indicators for unfavorable outcomes 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of metabolomics, research on the metabolomics of SCA is steadily increasing. At the animal level, researchers observed that targeting metabolic pathways such as kynurenine pathway 9 , ketone pathway 10 , mitochondrial energy 11 can attenuate brain injury after SCA, improve prognosis, and prolong survival in mice. Previous studies have also reported several circulating metabolite biomarkers in SCA patients: N-acetylaspartate/creatinine ratios, lactate levels, glucose level served as predictive indicators for unfavorable outcomes 12,13 .…”
Section: Introductionmentioning
confidence: 99%